The Development of Teaching Material Design for Automotive Electrical and Electronics Laboratorium Based on Automotive-SKKNI to Improve the Achievement of Standar Competencies of Polytechnic Students - I Komang Rusmariadi; I Putu Darmawa; I Putu Sastra Negara; Ketut Bangse (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
This progress report contains about the achievement of the implementation of the program of research in the development of teaching materials in the form of an integrated jobsheet. The second stage of the development will be done in 2018 with the goal to find: 1) the evaluation result from the expert, lectures, and students, 2)the obstacles during the try out, and 3) the feasibility of the jobsheet draft as a lab teaching material. Research using Dick & Carey development model, in review and test the research involving 2 experts, 7 course lecturerss,and 24 students in mechanical engineering department. Data obtained using questionnaire enclosed and open questionnaire . Data were collected in the form of comments and suggestions as well as the evaluation result toward the integrated jobsheet were analyzed by descriptive qualitative and quantitative improvement. The test results stated: 1) the content expert test is very decent; design / media expert is very decent; individual very decent ; small group is very decent; and field testing of students and lecturer decent and very decent. 2) components that need to be revised from the entire contents of the test results and instructional design experts to field test were:The contents of the summary should be more material-oriented than the summary of jobsheet parts, in addition to trouble shooting ignition problems, it is necessary to add maintenance material that is preventive maintenance, assessment rubrics for evaluation /practical tasks need to be made in more detail from simple to complex practices. Summary and evaluation analysis tools must be clear, the amount of test practice material so that there is a balance of theory and practice, the size of the book should be chosen for an elegant appearance, especially if proposed to ISBN. Based on test data and analysis of the abovementioned, teaching material draft can be declared eligible as the practical of teaching jobsheet. This research only reached the stage of formative evaluation on Jobsheet, it is expected in the future to do more research to determine its effectiveness in an effort to increase the competence of students.